An Insight into Banking Sector Mergers and Acquisition-BRICS Nations - Sushant Sant; Mousumi Bhattacharya (International Journal of Economics and Financial Issues, 2020)
The banking and financial services (BFSI) sector is one of the most crucial areas in any economy. It is fastest growing and the listed players in this space has given high returns to the investors over the last decade. Commercial banks in the Indian context have witnessed radical changes in terms of enormous progression in off-balance sheet risk management of financial assets, regulatory amendments, NPA recognition norms, significant consolidation of the financial sector and introduction of e-commerce norms and online banking. In this context, Indian economy is similar to the other economies of BRICS countries. These countries are emerging economies with higher GDPs and undertaking various reforms to boost the consumption, transparency and business needs. So, it is pertinent to evaluate the M&A activities that have taken in India and other BRICS countries and comparing the same. This paper analyses the M&A that have taken place in India and other BRICS countries based on certain fundamental parameters which are based on regulatory requirements, profitability and overall returns on investments. The results of these tests indicate that there is insignificant change in most of parameters during post-merger phase. Further, other parameters showed a negative effect of merger on acquirer during post-merger period.